2016
DOI: 10.3389/fpsyg.2016.01906
|View full text |Cite
|
Sign up to set email alerts
|

An Affective Neuroscience Framework for the Molecular Study of Internet Addiction

Abstract: Internet addiction represents an emerging global health issue. Increasing efforts have been made to characterize risk factors for the development of Internet addiction and consequences of excessive Internet use. During the last years, classic research approaches from psychology considering personality variables as vulnerability factor, especially in conjunction with neuroscience approaches such as brain imaging, have led to coherent theoretical conceptualizations of Internet addiction. Although such conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 80 publications
(105 reference statements)
1
44
0
1
Order By: Relevance
“…ANPS facets distinctly correlate with measures of white matter integrity in polydrug abusers (Unterrainer et al, 2017), a subject group with likely deviations in reward sensitivity. Recently, problematic use of internet and smartphone addiction were associated with high expression of FEAR and SADNESS, and to a lesser extent ANGER, and to low levels of CARE, PLAY, and SEEKING (Montag et al, 2016). Interestingly, the two reward sensitivity component ROIS clearly differentiated these personality facets so that Insatiability by Reward was associated with ANGER, FEAR, and SADNESS, while Openness to Rewards was, instead, related to SEEKING, PLAY, and CARE.…”
Section: Discussionmentioning
confidence: 99%
“…ANPS facets distinctly correlate with measures of white matter integrity in polydrug abusers (Unterrainer et al, 2017), a subject group with likely deviations in reward sensitivity. Recently, problematic use of internet and smartphone addiction were associated with high expression of FEAR and SADNESS, and to a lesser extent ANGER, and to low levels of CARE, PLAY, and SEEKING (Montag et al, 2016). Interestingly, the two reward sensitivity component ROIS clearly differentiated these personality facets so that Insatiability by Reward was associated with ANGER, FEAR, and SADNESS, while Openness to Rewards was, instead, related to SEEKING, PLAY, and CARE.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to normal controls matched for age, gender and education, individuals with gaming disorder were more likely to use maladaptive emotion regulation strategies in terms of lower cognitive reappraisal and higher expressive suppression, and revealed greater depression, anxiety and hostility (Yen et al, 2018). Using the Affective Neuroscience Personality Scales, a self-report measure of primary emotions, fear and sadness were demonstrated to be robust antecedents of different aspects of problematic Internet use in a community dwelling sample (Montag, Sindermann, Becker, & Panksepp, 2016). Spada and Marino (2017) tested a structural model and indicated that meta-cognitions and emotional regulation impacted separately on problematic Internet use among 380 youngsters, aged 13 to 20.…”
Section: Original Articlementioning
confidence: 90%
“…Clearly other important emotion theories exist, which could be applied to human-computer-interaction (e.g., affect control theory [116]). Nevertheless, we demonstrated in a recent article why an AN framework is in particular useful for a neuroscientific study of technology use: In Table 12 of the work by Montag et al, a detailed roadmap is provided helping to provide researchers with abundant transmitter/neuropeptide candidates to be tested underlying emotional aspects of human-computer interaction [117]. To our knowledge such a roadmap has not been provided by other emotion theories.…”
Section: Interaction Of Primary Emotional Systems With Digital Worldsmentioning
confidence: 99%